Teens` dreams of becoming professional athletes: the gender gap in youths` sports ambitions - Eriksen, I. M. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
In comparatively gender equal Norway, most boys and girls participate in sports at about equal rates. This apparent gender equality is investigated further: do young teens also profess equal ambitions of becoming professional athletes? Drawing on 81 interviews with 12- and 13-year-olds, the study suggest that the boys and girls make similar investments in sports, but there are clear gender differences in the ways they describe their future ambitions. The majority of the boys talk about wanting to become professional athletes and going `all in`, but very few of the girls do - the ambitious girls rather talk about skills development. The paper argues that cultural narratives thus shape young people`s self-understanding and ambitions, both boys and girls may suffer consequences of this: in a sports-internal logic, the girls may be given limited practical possibilities, resources and support - but boys may risk regret, disappointment and wasting time and resources.